Meio ambiente: um estudo das representações sociais de professores de biologia dos centros de excelência de Sergipe - Melo, Regineide Meneses (2014)
The study of social representations of the environment has been touted as an important tool to understand how a person or a particular group represents the environment and, in the case of teachers, such as Social Representations are relate practices and this theme. From this perspective, this qualitative research analytical and descriptive, has the main objective to identify the Social Representations of the environment of the biology teachers of Centro de Excelência de Sergipe, three located in Aracaju and one in Nossa Senhora da Glória, and check if there has a relationship between the social representations of these teachers and their speech about their practice. The theoretical framework contributes with theories of Moscovici (1978) as well as thinkers like Jodelet (2005), Reigota (2007) and Guimarães (2007), among others. The data collection instruments were a questionnaire and an almost structured interview. The subjects answers regarding the Social Representations of the environment were categorized from anthropocentric, naturalist and globalizing proposals Reigota (1995). Through the analysis of the contents obtained in the questionnaires and interviews, it was evident that 62.5% of teachers have studied a holistic representation of the environment, while 37.5% have a naturalist and anthropocentric representation. With regard to teaching practices developed, one notes that are concentrated in the construction of educational projects focusing on environmental issues. Teachers also cited a number of barriers that allows the practices concerned with environmental issues, such as lack of equipment and lack of student interest. It was also found that not all the teaching practices relate representations that teachers possess. These results show that although more than half of the teachers present a holistic view of the environment, there is still the need to build from initial a more complex design, where interactions involving the environment are beyond the ecological sphere. This broad vision will be passed on to students in the classroom, contributing to the formation of subjects who see themselves as members of the environment whose actions can affect the quality of that environment .